2016
DOI: 10.3892/or.2016.4864
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-23a downregulates the expression of interferon regulatory factor-1 in hepatocellular carcinoma cells

Abstract: Interferon regulatory factor-1 (IRF-1) is a tumor-suppressor gene induced by interferon-γ (IFNγ) and plays an important role in the cell death of hepatocellular carcinoma (HCC). HCC tumors evade death in part by downregulating IRF-1 expression, yet the molecular mechanisms accounting for IRF-1 suppression in HCC have not yet been characterized. Previous studies have shown that microRNA-23a (miR-23a) can suppress apoptosis by targeting IRF-1. Therefore, we hypothesized that miR-23a promotes HCC growth by down-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Yan et al . found that miR-23a was a negative regulator of IRF-1in HCC, which highlighted its importance in HCC initiation and progression135. Zhang et al .…”
Section: Discussionmentioning
confidence: 96%
“…Yan et al . found that miR-23a was a negative regulator of IRF-1in HCC, which highlighted its importance in HCC initiation and progression135. Zhang et al .…”
Section: Discussionmentioning
confidence: 96%
“…This up-regulation in liver cirrhosis than healthy controls and further up-regulation in HCC patients in comparison to viral hepatitis patients suggests a role of microRNA 23a in the pathogenesis of HCC. A study on resected human HCC tissues found that microRNA-23a down-regulates the expression of interferon regulatory factor-1 in HCC cells[ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SP1 transcriptional regulatory element is present within the TLR4, TNF-α, and TGF-β1 gene promoters, while the IRF1 transcriptional regulatory element is present within the IL10 gene promoter [20][21][22][23]. Furthermore, SP1 and IRF1 have been shown to be direct targets of miR-23a in previous studies [24][25][26]. Thus, it is reasonable to infer that miR-23a-3p could mediate the imbalance between TLR4/TNF-α pro-inflammatory and IL10/TGF-β1 anti-inflammatory pathways under Mtb stimuli via targeting SP1 and IRF1 directly.…”
Section: Discussionmentioning
confidence: 95%